Nutritional value and acceptability of heme iron microparticles-fortified bread - Rengifo, Estefany Deyhanyra (2025)
Iron deficiency anemia is a significant global health challenge, prompting the exploration of novel iron fortification strategies. This study investigated pectin microparticles coated with bovine blood as a heme iron source to fortify bread. Four treatments were prepared: control, ferrous fumarate fortified, and bread with 15% and 25% microparticles. The physicochemical characteristics (including iron content and peroxide values), microbial counts, and overall acceptability were analyzed. Results showed that adding microparticles significantly increased the iron content of the bread (7.77 ± 0.05 mg/100 g). Peroxide values remained below 3.43 meq O2/kg extracted fat, and mold counts were within acceptable limits (<10 CFU/g) for all treatments. A 7-point hedonic scale acceptability test in school-aged children (8–12 years) revealed no significant differences among treatments. Therefore, incorporating microparticles containing bovine blood-derived iron in bread offers a promising solution for producing iron-enriched food, providing a potential strategy for improving the health of school-age children.